Analysis of Student Error in Solving Number Theory Problems in View of Cognitive Style - Nur'aini Muhassanah (Universitas Wiralodra, 2023)
This research is a qualitative research using a descriptive approach. The purpose of this study was to describe the errors of mathematics students in working on number theory questions in terms of cognitive style. The subjects of this study were 3rd semester students of the Mathematics Study Program, Faculty of Science and Technology, Nahdlatul Ulama University, Purwokerto, with 3 students representing the Field Dependent (FD) group, 3 students entering the Field Intermediate (FDI) group, and 3 students representing the Field Independent (FI) group. Data related to student errors in working on number theory questions were obtained from diagnostic tests and interviews. While the cognitive style data obtained from the results of the Group Embedded Figure (GEFT) test. Subjects were taken by purposive sampling technique and data validation using triangulation method. The data analysis technique used data reduction, data presentation, and drawing conclusions. The results of this study for students in the FD category made a lot of procedural errors as much as 48.1%, for students in the FDI category many made conceptual errors as much as 33.3%, and students in the FI category made a lot of mistakes. technical errors as much as 25.9%. Furthermore, of the three categories of students according to cognitive style, the FD category made the most mistakes for all forms of conceptual, procedural, and technical errors. The most common form of error from all students studied was conceptual error as much as 44.4%. Many factors cause students to make mistakes in solving number theory questions, the most frequent mistakes are: 1) Students do not master and understand the concepts, theorems and definitions in number theory courses; 2) Students are not careful in calculations which causes the final result to be wrong; and 3) Students do not understand the problem in the problem so that it is difficult to solve.